Children reading of fiction in Siberian and Far Eastern libraries (late XX - early XXI centuries) - Y. V. Timofeeva (Библиосфера, 2016)
The article first gives a general view of children reading of fiction in Siberia and the Far East. The relevance of studying children reading is determined by its great social and pedagogical potential. The study objectives are: 1) to identify popular children genres of literature; 2) to recreate the repertoire of favorite authors and their works; 3) to compare the range of reading of Siberian and Far Eastern young people with the reading of their age mates from other regions of the country; 4) to identify main factors forming readers demand of the younger generation. The study has shown that fairy tales, fantasy, detectives, adventures, historic and love stories are the most popular among children. National and foreign writers of the XIX - early XXI centuries are called among the children's favorite authors: A. Barto, M. Bulgakov, A. Volkov, A. Green, A. Dumas, A. Ishimova, A. Lindgren, S. Marshak, A. Milne, N. Nosov, A. Pushkin, M. Reed, M. Twain, L. Charskaya, E. Uspensky and many others. The comparison was made between reading literature by children from Transurals and the European part of Russia. Similarity in the repertoire of reading, favorite genres and authors is proved. Selection of literary works is determined by children personal interests and the curriculum content. Therefore, reading fiction is both leisure and business. Reading fiction on the pupils’ personal choice is usually considered as leisure. Reading literature for educational purposes is related to business. The article pays attention to the difficulty of separating leisure reading from business one when it concerns reading fiction by students. Growing readers’ interest in picturized literary works is marked. This article was written on a wide range of sources and research literature.